Quality of Life of Postmenopausal Women Residing in Lalitpur District, Nepal - Lalita Bhatt; Prakash Ghimire; Alisha Khadka; Min Raj Joshi; Tina Gurung; Laxmi Gurung (Journal of Holistic Nursing and Midwifery)
Introduction: Hormonal imbalance due to menopause may cause physical, psychosocial, sexual, and vasomotor symptoms that can hinder the quality of life (QoL) of postmenopausal women. In Nepal, postmenopausal women are at potential risk of decreased QoL since it is a patriarchal society and gives low priority to women Objective: This research aimed to evaluate the QoL of postmenopausal women residing in Lalitpur district, Nepal. Materials and Methods: This is a community-based analytical study with a cross-sectional design conducted on 215 postmenopausal women aged 45-60 years residing in Mahalaxmi municipality of Lalitpur district, Nepal, who were selected using a systematic random sampling technique. The Menopause-specific QoL (MENQOL) questionnaire was used to collect data through face-to-face interviews. Descriptive statistics and the chi-square test were used to analyze the collected data. Results: The mean age of women was 54.51±3.83 years. The majority of them were married (87.4%), living in a joint family (74%) and illiterate (66%). Among women, 98.6% had experienced at least one menopausal symptom based on the MENQOL domains. Also, 62.8% had moderate QoL, 20.2% had good QoL and 17% had poor QoL. The level of QoL was significantly different based on occupation (P=0.03) and age at menarche (P=0.003). Conclusion: Menopausal symptoms are dominant among postmenopausal women in Nepal, among which physical symptoms are the most common, and vasomotor symptoms are the least common symptoms. It is recommended that effective interventions be planned and implemented to improve the QoL of Nepali postmenopausal women.